Collaboration toolkit for Web-Based visual analytics applications (2016)
One of the relevant trending challenges in the field of collaborative visualization is the need of standardizing the design and implementation of collaborative features in the workflow of applications of Visual Analytics. Furthermore, given the increasing tendency and evolution of web based technologies applied to visual analytics, we propose and implement a web-based toolkit intended to shorten the time and effort of development for the integration of collaborative features in Web-based applications of Visual Analytics. The toolkit, including a set of selected functionalities based on the conclusions of previous research, in conjunction with a proposed integration workflow for developers, is contrasted to other solutions with different approaches in a similar context. Finally, the impact of our solution is briefly discussed in the context of 2 selected cases of use.